Urgensitas Pembinaan Orang Muda Katolik terhadap Bahaya Krisis Identitas - Nanik Wijiyati Aluwesia; Alfonsius Yoga Pratama; Antonius Denny Firmanto (VOCAT: JURNAL PENDIDIKAN KATOLIK, 2022)
The focus of this article is on the theme of fostering the faith of young Catholics in the face of identity crisis. The purpose of this study is to find out the answer to the question: what is the situation and dynamics of young people? What is an identity crisis and its accompanying consequences? How important and urgent is the fostering of faith in young Catholics facing the brink of an identity crisis? The results suggest that young people are in a transition to adulthood. They begin to think of abstract things and let go of childhood thinking. Restraints and prohibitions will make them inauthentic personalities. An identity crisis is a phase in which a person experiences confusion to determine one's identity. The consequences that occur when a person experiences an identity crisis are depression, delinquency and drug abuse. Young people desperately need the support of authoritative adults. A young person's companion must be a person who is in love with young people, mobilizer and persuasive. A good shepherd figure is a longing for them to get edification and injections of spirit, as well as bring positive energy. The study of this theme uses theological discourses and positive sciences. The method used is critical analysis and reading from various sources such as Church documents and sources from other positive science. The findings in this study are the usefulness of the development and mentoring of faith in young Catholics in the face of the dangers of identity crisis